2021
DOI: 10.1182/blood-2021-152208
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the Don't Eat Me Signal (CD47-SIRPα Axis) to Improve Antibody-Based Immunotherapy of Multiple Myeloma

Abstract: The addition of monoclonal antibodies daratumumab, elotuzumab and isatuximab to the treatment of patients with multiple myeloma significantly improved the outcome and prolonged survival. Unfortunately, although many patients benefit, depth and duration of response are a problem. In order to improve efficacy of antibody-based immunotherapy, we aimed to combine CD38-directed antibodies daratumumab and isatuximab as well as SLAMF7-targeting elotuzumab with a CD47 blocking antibody to enhance phagocytosis of myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…CD47 mAb or CD38 mAb is effective for the treatment of MM [ 92 , 113 , 184 ]. Significantly, blocking the CD47/SIRPα signaling pathway enhanced the killing effect of CD38 mAb on MM cells [ 112 ]. Based on this, the design of BsAbs targeted both CD47 and CD38 may have a synergistic effect in the treatment of MM.…”
Section: Cd47/sirpα-targeted Bispecific Antibodies (Bsabs)mentioning
confidence: 99%
See 1 more Smart Citation
“…CD47 mAb or CD38 mAb is effective for the treatment of MM [ 92 , 113 , 184 ]. Significantly, blocking the CD47/SIRPα signaling pathway enhanced the killing effect of CD38 mAb on MM cells [ 112 ]. Based on this, the design of BsAbs targeted both CD47 and CD38 may have a synergistic effect in the treatment of MM.…”
Section: Cd47/sirpα-targeted Bispecific Antibodies (Bsabs)mentioning
confidence: 99%
“…Preclinical studies have demonstrated that blocking the CD47/SIRPα signaling pathway significantly enhances the killing effect of macrophages on MM in vitro and in vivo [110][111][112]. While clinical trials for the role of CD47 mAb in MM are relatively rare, none of eight patients with MM enrolled in a phase I clinical study (NCT02663518) of TTI-621 achieved ORR.…”
Section: Multiple Myeloma (Mm)mentioning
confidence: 99%